2017
DOI: 10.3904/kjim.2016.268
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of liver cirrhosis: current evidence and expectations

Abstract: In the past, liver cirrhosis was considered an irreversible phenomenon. However, many experimental data have provided evidence of the reversibility of liver fibrosis. Moreover, multiple clinical studies have also shown regression of fibrosis and reversal of cirrhosis on repeated biopsy samples. As various etiologies are associated with liver fibrosis via integrated signaling pathways, a comprehensive understanding of the pathobiology of hepatic fibrogenesis is critical for improving clinical outcomes. Hepatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(79 citation statements)
references
References 137 publications
1
65
0
10
Order By: Relevance
“…The evidence available so far demonstrated that, regardless of HBeAg‐positive or HBeAg‐negative status, antiviral‐induced and natural remission of liver inflammation can lead to regression of fibrosis, but the reversibility of cirrhosis accompanied by architectural alteration of liver remains controversial . Therefore, the identification of significant fibrosis prior to cirrhosis is a key factor for effective management of CHB.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence available so far demonstrated that, regardless of HBeAg‐positive or HBeAg‐negative status, antiviral‐induced and natural remission of liver inflammation can lead to regression of fibrosis, but the reversibility of cirrhosis accompanied by architectural alteration of liver remains controversial . Therefore, the identification of significant fibrosis prior to cirrhosis is a key factor for effective management of CHB.…”
Section: Discussionmentioning
confidence: 99%
“…Cirrhosis is the advanced stage of chronic hepatitis, being the result of imbalanced production (decrease) and destruction (increase) of the hepatocellular matrix [32][33][34]. Identifying patients with advanced fibrosis or beginning cirrhosis is clinically relevant, as it serves as a crucial determinant in the evaluation of disease progression, therapy response, and longterm outcome [5-8, 35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…5,18,19 Restitution of LP or a potentially reversible process of iron overload has been recently discussed and may play a role. 20 But, a complete recovery was not observed in any patient within the study period. In patients with thalassemia, cellular iron uptake is downregulated through hepcidin after many transfusions.…”
Section: Discussionmentioning
confidence: 84%
“…The probable causes are iron loss or regeneration of LP and the well‐described downregulation of iron transporting proteins . Restitution of LP or a potentially reversible process of iron overload has been recently discussed and may play a role . But, a complete recovery was not observed in any patient within the study period.…”
Section: Discussionmentioning
confidence: 94%